Dan Flavin : the architecture of light - Flavin, Dan, 1933-1996; Solomon R. Guggenheim Museum (New York : The Solomon R. Guggenheim Foundation, 2000)
"Dan Flavin (1933-1996) has long been recognized for his pioneering use of light and color divorced from traditional artistic contexts. Employing only commercial fluorescent lights, Flavin devised a radical new art form that circumvented the limits imposed by frames, pedestals, and other conventional means of display." "This book, published on the occasion of Dan Flavin: The Architecture of Light at the Deutsche Guggenheim Berlin, draws upon the Solomon R. Guggenheim Museum's extensive holdings of the artist's work." "Dan Flavin: The Architecture of Light provides a wide-ranging view of Flavin's work and intellectual thought, bringing together contributions by Tiffany Bell, Frances Colpitt, Jonathan Crary, Michael Govan, Joseph Kosuth, Michael Newman, J. Fiona Ragheb, and Brydon E. Smith, with excerpted writings by the artist. This volume is richly illustrated with selections from the Solomon R. Guggenheim Museum's collection of Flavin's fluorescent constructions, as well as installation views from the Museum's long-standing history of exhibiting the artist's work."--Jacket
-- Of Situations and Sites / J. Fiona Ragheb -- the nominal three (to William of Ockham) / Joseph Kosuth -- monument on the survival of Mrs. Reppin / Frances Colpitt -- greens crossing greens (to Piet Mondrian who lacked green) / Michael Govan -- an artificial barrier of blue, red and blue fluorescent light (to Flavin Starbuck Judd) / Brydon E. Smith -- untitled (to Jan and Ron Greenberg) / Jonathan Crary -- untitled (fondly to Margo) / Tiffany Bell -- untitled (to Barbara Nusse) / Michael Newman -- Writings / Dan Flavin -- Biography -- Bibliography / Kara Vander Weg
"Published on the occasion of the exhibition Dan Flavin: the architecture of light, organized by J. Fiona Ragheb, Deutsche Guggenheim Berlin, November 6, 1999-February 13, 2000"--Title page verso
Includes bibliographical references
Keywords: Flavin, Dan, -- 1933-1996 -- Exhibitions; Light in art -- Exhibitions; Installations (Art) -- Exhibitions